Differences of a Single Injection of Botulinum Toxin A between Infantile and Nonaccommodative Esotropia. Issue 3 (2nd July 2020) - Gama, Rita; Santos, Joana Chambel; Nom, Tânia Yang; Costa, Daniela Cândido da
ABSTRACT: Purposes: To compare the results of a single injection of botulinum toxin A (BTA) between children with infantile esotropia (IET) and nonaccommodative esotropia (NAET) during the first 2 years. Methods: Retrospective study that included 23 children with IET and 25 with NAET. At 6 months, 1 and 2 years after treatment, the deviation and stereoacuity were evaluated. Results: At 6 months and 1 year after treatment there was no difference in ocular alignment between the two groups (success criteria were achieved in 36.8% in IET group and 60.0% in NAET at 6 months p = .129, and 57.9% in IET group and 68.0% in NAET group at 1 year p = .352). Two years after treatment, there were statistical differences between motor alignment (IET group 21, 1% and NAET group 60.0%, p = .007) and stereoacuity (IET group 40% and NAET group 90%, p = .004) between the two groups. Although side-effects affected most children during the first week (in the first week, overcorrection was present in 16 (84.2%) children with IET, and in 19 (76.0%) children with NAET; and ptosis affected 15 (78.9%) children with IET and 17 (68.0%) children with NAET), at 6 months all the effects have disappeared on both groups. Conclusions: We recommend BTA as an alternative, but not as definite treatment in IET if the surgeon/parents are not comfortable with an early strabismus surgery; but retreatment or surgery will have to be considered after 1 year. On the contrary, BTA may be a first-line treatment of NAET because it is an easy, safe and has a long-lasting effect.